2011
DOI: 10.32607/20758251-2011-3-1-107-115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Myocardial Infarction in Mice: Methodology, Monitoring, Pathomorphology

Abstract: Myocardial infarction is one of the most serious and widespread diseases in the world. In this work, a minimally invasive method for simulating myocardial infarction in mice is described in the Russian Federation for the very first time; the procedure is carried out by ligation of the coronary heart artery or by controlled electrocoagulation. As a part of the methodology, a series of anesthetic, microsurgical and revival protocols are designed, owing to which a decrease in the postoperational mortality from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Through the GSEA analysis, it was found that PTX3 was significantly linked to the production of IL-6. Furthermore, IL-6 is a key activator of STAT3, a protein that is important in cardiac physiology and pathology [ 14 ]. As a result, it is hypothesized that PTX3 may play a role in the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the GSEA analysis, it was found that PTX3 was significantly linked to the production of IL-6. Furthermore, IL-6 is a key activator of STAT3, a protein that is important in cardiac physiology and pathology [ 14 ]. As a result, it is hypothesized that PTX3 may play a role in the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The apical four chamber view was taken, the mitral valve flow spectrum was measured by PWD, and the peak velocity of early diastolic flow (E) and late diastolic flow (A) were recorded; M-mode color Doppler images of mitral valve orifice were recorded to obtain the left ventricular blood flow propagation velocity in the early diastole; After obtaining satisfactory parasternal long axis, color blood flow was used to locate the left atrial entrance of pulmonary vein, obtain the spectrum of pulmonary vein, and record the peak velocity of pulmonary vein in systole (PVS), positive peak velocity of pulmonary vein in diastole (PVD) and negative peak velocity of pulmonary vein in atrial systole (PVA) to evaluate the diastolic functions. ECG were used to diagnose the myocardial infarction, mice were put in a supine position and connected to three electrodes: one on the left foreleg, one on the right foreleg, and one on the right hind leg and then the ECG was recorded [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECG recordings of age-matched Xirp2 +/+ and Xirp2 À/À littermates were performed under anesthesia with sodium pentobarbital (50 mg/kg, intraperitoneally) as described previously. 46 ECG signals were recorded with an ECG amplifier and recorder (RS3400; Gould Instruments, Basingstoke, UK). ECG parameters, such as P wave, QRS, QT, and R-R intervals, were calculated from ECG tracings as described previously.…”
Section: Ecg Recordingsmentioning
confidence: 99%
“…Animal models of ischemic heart disease hold great importance, both in exploring novel mechanisms and for the development of future successful therapeutic interventions that can be clinically translated. Despite alternative AMI models that have been proposed and studied during recent years, including chemical 3 , radiofrequency 4 , thermal 5 or cryogenic injuries 6 , permanent left descending coronary artery (LAD) occlusion remains the most common model used by researchers 7 .…”
Section: Introductionmentioning
confidence: 99%